PID Control for Linear and Nonlinear Industrial Processes - Shamsuzzoha, Mohammad; Lloyds Raja, G. (IntechOpen, 2023)
A proportional-integral-derivative (PID) controller is an instrument used in industrial control applications to regulate process variables such as temperature, pressure, flow, etc. PID controllers are still very much preferred in the industry due to their simplicity and ability to yield reasonable closed-loop performance. About 90% of industrial controllers are of the PID type. To meet the continuously evolving challenges in industrial process control, it is essential to formulate PID-based control strategies which can yield improved performance. The contents of this book will serve as a good introduction to PID controllers and equip readers to design such controllers for various industrial applications.